2021
DOI: 10.1039/d1tc04680b
|View full text |Cite
|
Sign up to set email alerts
|

Cohosts with efficient host-to-emitter energy transfer for stable blue phosphorescent organic light-emitting diodes

Abstract: We present a high-performance blue phosphorescent organic light-emitting diode exhibiting a low operating voltage (4.1 V), high external quantum efficiency (23.4%, at 500 cd m−2) with a low efficiency roll-off (4.7%), and a long operation lifetime (time at which the luminance reaches 95% of its initial value, LT95 = 232 h).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This is because the TADF material’s strong intramolecular charge transfer characteristics lead to red-shifted emission behavior, which in turn results in higher bandgap and triplet energy characteristics. These higher energy values can cause some reduction in the device stability of blue TADF OLEDs 6 , 8 . As a result, phosphorescence and TADF materials have emerged as potential candidates for deep blue OLEDs because of their longer device lifetime and higher color purity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the TADF material’s strong intramolecular charge transfer characteristics lead to red-shifted emission behavior, which in turn results in higher bandgap and triplet energy characteristics. These higher energy values can cause some reduction in the device stability of blue TADF OLEDs 6 , 8 . As a result, phosphorescence and TADF materials have emerged as potential candidates for deep blue OLEDs because of their longer device lifetime and higher color purity.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, phosphorescence and TADF materials have emerged as potential candidates for deep blue OLEDs because of their longer device lifetime and higher color purity. Later, Choi et al reported a long-lifetime blue phosphorescent OLED employing the CN-Ir(III) dopant 8 . This device exhibited LT 95 of 232 h at an initial luminescence of 500 nits with a maximum EQE of 25.1% by using an optimized exciplex host combination system, which could have good charge balance and efficient energy transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%